Adapting to the therapeutic recommendations of patients treated of type 2 diabetes - Natalia Alicja Świątoniowska; Beata Jankowska-Polańska (Journal of Education, Health and Sport, 2017)
Introduction.  Year after year, more and more people are suffering from diabetes, the number  of people with diabetes in 2012 confirms its fourfold increase over the last 35 years. It is estimated that in 2035, diabetes will be diagnosed in every third person. Currently the treatment of type 2 diabetes is based on glycemic control and avoidance  of complications. These goals can be achieved through lifestyle changes, the use  of hypoglycaemic drugs, and insulin injections. Achieving correct glycemic control is only possible if patients follow therapeutic recommendations. Data in the literature indicate that only 50% of patients follow established therapeutic regimens.